Archery skill indexes: estimation of archers' performance level by using forearm surface EMG data - Ertan, H.; Soylu, A. R.; Korkusuz, F. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of the current study was to create some archery skill indexes that could be used in estimation of archers' performance levels by using forearm surface EMG data. It is concluded that archery skill indexes may be used for a) evaluation of archers' progress, b) selection of talented archers and c) improvement of archers' progress. Naturally, future researches will determine the application of archery skill indexes into practice.